2001
DOI: 10.1080/03079450120078725
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vaccine deposition site on post-vaccinal viraemia and vaccine efficacy in broiler chickens followingin ovovaccination against Marek's disease

Abstract: In ovo vaccination against Marek's disease is a widely used technology in the broiler industry. A series of experiments was carried out to determine the site of vaccine deposition in the egg during automated in ovo vaccination, and the effect of vaccine deposition site and dose on vaccine responses following vaccination with cell-associated herpesvirus of turkeys in commercial broiler chickens. Vaccine deposition site following automated in ovo vaccination was principally influenced by the age of embryo, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…First, LW reduction in this study was observed from day 28 onwards, but has been reported by day 7 in SPF chickens (Witter et al, 1980). Second, the onset of first MDV-related mortality occurred at days 33 to 35 post-challenge in our other experiments using the same virus and chickens as these experiments (Islam et al, 2001a), but has been reported as early as days 7 to 16 post-challenge in other studies (Witter et al, 1980(Witter et al, , 1999. Whether this delay in pathogenesis is due to the maternal antibody in our birds, their difference in genotype, or a combination of these cannot be resolved from these studies.…”
Section: Discussioncontrasting
confidence: 46%
“…First, LW reduction in this study was observed from day 28 onwards, but has been reported by day 7 in SPF chickens (Witter et al, 1980). Second, the onset of first MDV-related mortality occurred at days 33 to 35 post-challenge in our other experiments using the same virus and chickens as these experiments (Islam et al, 2001a), but has been reported as early as days 7 to 16 post-challenge in other studies (Witter et al, 1980(Witter et al, , 1999. Whether this delay in pathogenesis is due to the maternal antibody in our birds, their difference in genotype, or a combination of these cannot be resolved from these studies.…”
Section: Discussioncontrasting
confidence: 46%
“…Although it was highly pathogenic in unvaccinated chickens, inducing MD lesions in 84% of at-risk unvaccinated chickens, vaccination with HVT provided complete protection against these lesions. We have observed complete protection with HVT previously with this strain in commercial broilers, although protection of 70 to 80% is more typical (Islam et al, 2001(Islam et al, , 2008. Given these findings, the provisional virulence ranking of very virulent ascribed to this virus by De Laney et al (1998) cannot be supported.…”
Section: Discussionmentioning
confidence: 99%
“…The VCI is an important determinant of efficacy for all live viral vaccines (Alexander et al, 2006) as longer intervals enable more time for vaccinal virus replication and the mounting of an effective adaptive immune response. HVT has been used as a vaccine against MD in broiler chickens since 1971, and since the early 1990s it has been increasingly administered in ovo 3 to 4 days before hatch using automated egg handling and injecting systems (Sharma & Burmester, 1982;Ricks et al, 1999;Islam et al, 2001). Part of the rationale for in ovo vaccination is to provide additional time for the development of an effective immune response before challenge, which is commonly assumed to be early in the life of the chicken.…”
Section: Introductionmentioning
confidence: 97%